Are trans-national Professional Development Programmes doomed to fail to influence student outcomes? - Karen Hudson; David Littlefair; Joanne Clifford-Swanc (European Teacher Education Network, 2020)
Trans-national education is increasing (Mahony, 2014) and with regard to professional development for teachers, is an important aspect of upskilling teachers to deliver high quality learning experiences for their pupils. This paper is concerned with Trans-national Professional Development delivered by one UK HEI and delivered to Chinese Teachers. In the Chinese context, the need for such professional development is rooted in the Ministry of Education's (2010) vision for developments, which will lead to a shift from an exam orientated education system to one that is quality orientated. The university has engaged with a number of different regions in China to deliver professional development for their teachers and head teachers in this vein. Although on the surface, positively received, participants identified a number of barriers that constrained the impact of the professional development. This article explores the pedagogical, cultural and investment barriers that led some participants to perceive that it was impossible to implement new strategies in their context. Insight of this nature can support institutions to tailor their international professional development programmes towards a model of input coupled with continued professional support to increase the potential for training to have an impact on practice and children's educational experiences.